Association between phenotypic and genotypic characteristics and disease severity in individuals with cystic fibrosis - Carneiro,Gabriella Vieira (2023)
Abstract Objective: To analyze the association between phenotypic and genotypic characteristics and disease severity in individuals with cystic fibrosis treated at a reference center in Minas Gerais, Brazil. Methods: This is a retrospective study that collected clinical and laboratory data, respiratory and gastrointestinal manifestations, type of treatment, Shwachman-Kulczycki score, and mutations from the patients’ medical records. Results: The sample included 50 participants aged one to 33 years, 50% of whom were female. Out of the one hundred alleles of the Cystic Fibrosis Transmembrane Conductance Regulator gene, the most prevalent mutations were DeltaF508 (45%) and S4X (18%). Mutation groups were only associated with pancreatic insufficiency (p=0.013) and not with disease severity (p=0.073). The latter presented an association with colonization by Pseudomonas aeruginosa and Staphylococcus aureus (p=0.007) and with underweight (p=0.036). Death was associated with age at diagnosis (p=0.016), respiratory symptomatology (p=0.013), colonization (p=0.024), underweight (p=0.017), and hospitalization (p=0.003). Conclusions: We could identify the association of mutations with pancreatic insufficiency; the association of Staphylococcus aureus colonization and underweight with disease severity; and the lack of association between mutations and disease severity. Environmental factors should be investigated more thoroughly since they seem to have an important effect on disease severity.